Accelerators to reduce violence, HIV risk, and early pregnancy among adolescents and young people in Namibia: A cross-sectional analysis of the Violence Against Children & Youth Survey. - Madison T Little; Lucas Hertzog; William E Rudgard; Elona Toska; Boladé Banougnin; Rachel Yates; David Chipanta; Francis B Annor; Laura Chiang; Lucie Cluver (PLOS Global Public Health)
Our study applied the INSPIRE Framework - the WHO's 2016 technical package of evidence-based interventions for addressing violence against children - to identify accelerators for youth in Namibia. Accelerators are protective factors that contribute toward achieving multiple SDG targets. Using nationally representative data from the 2019 Namibia Violence Against Children & Youth Survey (n = 5167), three hypothesised accelerators (food security, parental support, and gender-equitable attitudes) were investigated for their impact on 12 adolescent outcomes. Associations between the hypothesised accelerators and outcomes were assessed using multivariable logistic regressions, and adjusted probabilities, differences, and ratios. Among girls, food security, gender-equitable attitudes, and parental support were accelerators, being associated with lower odds for 8, 6, and 2 outcomes, respectively. When all three were present, the combination was significantly associated with 10 out of 12 outcomes, including >75% lower prevalences of child marriage; > 50% lower prevalences of child abuse, sexual violence victimisation, early sexual debut/early pregnancy, and peer violence victimisation; and >25% lower prevalences of intimate partner violence (IPV) victimisation, not being in school or paid work, mental health distress, inconsistent condom use, and age-disparate or transactional sex. Among boys, gender-equitable attitudes was an accelerator and was significantly associated with 7 out of 10 outcomes, including approximately 50% lower prevalences of sexual violence victimisation, child abuse, age-disparate or transactional sex, IPV victimisation, multiple sexual partners, peer violence victimisation, and inconsistent condom use. Adolescents (especially girls) with access to INSPIRE provisions experience lower rates of violence and HIV-related risks. Implementing interventions on these priority protective factors could accelerate progress in achieving the SDGs for adolescents and young people in Namibia.